The importance of water depth distribution maps in the sprinkler irrigation system performance assessment - Rezayati, Amir Mohammad; Liaghat, Abdolmajid; Sharifipour, Majid; Ghameshlou, Arezoo N. (Water science & technology. Water supply, 2023)
The assessment of sprinkler system performance is crucial in ensuring the efficient use of water resources. The commonly used indicators of the uniformity of water distribution in sprinkler systems are Christiansen's uniformity (CU) and distribution uniformity (DU) coefficients. A more comprehensive analysis of water distribution is essential in situations where the reliability of these coefficients as indicators of water distribution patterns is limited. In the present research, distribution maps of water depth were prepared from water application profiles using catch cans experiments that were carried out in the research farm of the Agriculture and Natural Resources Faculty of the University of Tehran, which is located in Alborz province. In this way, water application profile data were obtained at different operating pressures (200, 250, 300, 350, and 400 kPa). By using this data, 2D and 3D distribution maps of water depth were created due to the overlapping of sprinklers in different arrangements, spacing, and pressures. In addition, CU and DU coefficients in square, rectangular, and triangular arrangements with different spacing and pressures from 200 to 400 kPa. A total of 11,250 different simulations were calculated and analyzed. Distribution maps of water depth contribute to advancing the understanding of sprinkler irrigation system performance and aid in the optimization of water management practices.